1996
DOI: 10.1074/jbc.271.19.11518
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of HuD, a Neuronal RNA-binding Protein

Abstract: HuD is a human neuronal specific RNA-binding protein. In this study we have purified HuD and examined its RNA binding properties in detail. HuD binds to mRNAs that contain an AU-rich element with high affinity. In the case of the c-fos AU-rich element, HuD binds to a 27-nucleotide core element comprising AUUUA, AUUUUA, and AUUUUUA motifs. Mutation in any two of these motifs abrogates binding. HuD contains two tandem RNA recognition motifs (RRM), a basic domain, and a third RRM. Deletion analysis has shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
160
2
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(171 citation statements)
references
References 44 publications
7
160
2
2
Order By: Relevance
“…However, only the 36-kDa protein was cytoplasmic and therefore seemed the most likely one to be involved in mRNA polyadenylation in embryos. Members of the ELG family encode proteins that bind U-rich sequences in cytokine mRNAs similar to the eCPE and that range in size from 36 to 42 kDa (1,4,21,22). In Xenopus, several ELGs are expressed in the oocyte and early embryo (10).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only the 36-kDa protein was cytoplasmic and therefore seemed the most likely one to be involved in mRNA polyadenylation in embryos. Members of the ELG family encode proteins that bind U-rich sequences in cytokine mRNAs similar to the eCPE and that range in size from 36 to 42 kDa (1,4,21,22). In Xenopus, several ELGs are expressed in the oocyte and early embryo (10).…”
Section: Resultsmentioning
confidence: 99%
“…Other members of the ELAV family, such as Hel-N1 (the human homolog of ElrB) and HuD (the human homolog of ElrD), are known to bind to AU-rich elements (4,6). To rule out the possibility that ElrA binds to Cl2 RNA simply because of its affinity to AU-rich sequences, we performed a gel retardation assay using the histone B4 3Ј UTR (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Previous in vitro studies on Hu proteins have shown that RBDs 1 and 3 are required for binding to AREs and the poly(A) tail, respectively (Abe et al 1996b;Chung et al 1996;Ma et al 1997). Therefore, the binding of HuD to some speci®c ARE-containing mRNAs and also possibly the export of the mRNAs to the cytoplasm by shuttling may be involved in the induction of neurite outgrowth.…”
Section: The Novel Nes Of Hud and The Nucleocytoplasmic Shuttling Of mentioning
confidence: 99%
“…Likewise, hNT2 cells when induced to differentiate by retinoic acid exhibited a marked increase in the expression of human ELAV-like proteins which colocalized with mRNPs associated with polysomes (1). Hence, data from both of these studies support an important role for mammalian ELAV-like proteins in the processes of cell growth and differentiation.Interestingly, members of the ELAV family have been shown to bind the AU-rich regions of the 3ЈUTRs in cytokine and proto-oncogene mRNAs (5,14,27). In vitro binding studies with Hel-N1 documented preferential binding to the 3ЈUTRs of mRNAs which have short stretches of uridylate residues; however, in vivo RNA targets of ELAV proteins have not been identified (27).…”
mentioning
confidence: 99%